A convenient synthesis of cadmium chalcogenide quantum dots from cadmium acetate and bis(diphenylphosphino)methane monosulfide and –selenide or 1, 4-bis(diphenylphosphino)butane monoselenide. (3rd May 2016) - Faller, J. W.; Parr, Jonathan
GRAPHICAL ABSTRACT: ABSTRACT: The synthesis of both cadmium selenide and cadmium sulfide quantum dots has been effected using a synthetic protocol that avoids the use of volatile, toxic organocadmium reagents and alkyl phosphines.